Association of Ellis Class 2 fracture in 13–17 years old children - S B Sree Lakshmi; Lakshimi Lakshmanan (Journal of Advanced Pharmaceutical Technology & Research, 2022)
The objective of the study is to evaluate the association of Ellis Class 2 fracture in children aged between 13 and 17 years. This is a descriptive study that was carried out in a university context, using data from patients with Ellis Class 2 fractures between 13 and 17 years from June 2019 to February 2021, which were obtained by analyzing patient records. The records were transferred to the SPSS software for statistical analysis. The association of Ellis Class 2 fracture is common in relation to 11 which is about 29.41% and more common among the age group of 14 years and had a more male prediction. The knowledge of Ellis Class 2 fracture and its association with several parameters are essential in dentistry for various clinical performances. This can be accomplished by increasing awareness through Continuing Dental Education (CDE) programs, demonstrations, and seminars on the clinical regime of Ellis Class 2 fracture.